A Description of Clot Retraction as a Visual Experience - Ballerini, Giorgio; Seegers, Walter H (Thrombosis and Haemostasis, 1959)
Clot retraction is reviewed as a visual experience from the elementary considerations to more complicated and uncertain perspectives. The extent of retraction is dependent upon temperature, cell volume, surface contact, pH, fibrinogen concentration, thrombin concentration, calcium ion concentration, and platelet concentration. Platelets function in their own unique way. This quality is lost by such treatment as dialysis, ultrasonic waves, storage, and freezing. In the latter case there is some protection in glycerol solutions. Plasma contains dialyzable material concerned with clot retraction. This includes glucose and phosphorous, and perhaps other substances. Moreover, plasma contains one or more proteins of interest in clot retraction, and this protein(s) can be adsorbed on barium carbonate and eluted with sodium citrate solution. There may be clot retraction without the dialyzable material of plasma if the nondialyzable protein(s) are present and vice versa. The work is illustrated extensively with photographs and variables are considered in terms of three dimensional projection. In addition the ideas reviewed were developed in terms of information obtained with time lapse motion picture photography.